GABAC-Receptor Stimulation Activates cAMP-Dependent Protein Kinase via A-Kinase Anchoring Protein 220 - Li Yang; Yasuhisa Nakayama; Naoki Hattori; Bing Liu; Chiyoko Inagaki (Elsevier, 2008)
In our previous study, anti-apoptotic effects of GABAC-receptor stimulation was suppressed by inhibitors of cAMP-dependent protein kinase (PKA), implying GABACreceptor-mediated PKA activation. The present study showed that GABAC-receptor stimulation with its agonist, cis-4-aminocrotonic acid (CACA), protected cultured hippocampal neurons from amyloid β 25 -35 (Aβ 25 -35) peptide-enhanced glutamate neurotoxicity. This protective effect of CACA was blocked by PKA inhibitors, KT 5720 and H-89, as well as a specific GABAC-receptor antagonist, (1,2,5,6-tetrahydropyridine-4-yl) methylphosphinic acid (TPMPA). To test the possibility of GABACreceptor-mediated PKA activation, association of GABACreceptor with A-kinase anchoring proteins (AKAPs) and effect of an AKAP antisense oligonucleotide on the PKA activation were examined in primary cultured rat hippocampal neurons. Stimulation of the cells with CACA-activated PKA was assessed by the phosphorylated PKA substrate (135 kDa) level. Specific antibodies raised against GABAC-receptor ρ subunits precipitated each ρ subunit, AKAP220, and PKA regulatory and catalytic subunits from rat brain lysates, suggesting that ρ is associated with the AKAP220/PKA complex. Furthermore, antisense oligonucleotide of AKAP220 suppressed such GABACstimulation-induced PKA activation, suggesting that GABAC-receptor stimulation activates PKA via AKAP220. Keywords:: GABACreceptor, cAMP-dependent protein kinase (PKA), A-kinase anchoring protein 220 (AKAP220)